Clinical utility of liquid biopsy in canine oral malignant melanoma using cell-free DNA - Tagawa, Michihito; Aoki, Minori (Frontiers in Veterinary Science, 2023)
Introduction: Cell-free DNA (cfDNA), an extracellular free DNA released into the bloodstream by cells, is a potentially useful noninvasive marker to detect human malignancies and monitor response to treatment. In the present study, we evaluated the utility of circulating cfDNA in canine patients with oral malignant melanoma (OMM) in assessing therapeutic response and clinical outcomes. Methods: Plasma samples were collected from 12 dogs with OMM and 9 healthy controls. cfDNA concentration was quantified by real-time PCR resulting in short (99bp) and long (218bp) fragments of long interspersed nuclear element-1 (LINE-1), and the DNA integrity index (DII) was then calculated (218/99). A follow-up study was conducted on 6 dogs with OMM, and the plasma cfDNA and DII were quantified throughout disease progression. Results: Although cfDNA levels obtained from dogs with OMM were not significantly different compared to those obtained from healthy controls, the DII was signiﬁcantly lower in dogs with OMM than in healthy controls. The DII tended to decrease as the disease stage progressed. Moreover, changes in cfDNA concentration and DII along the clinical course were observed when major changes, such as metastasis or apparent tumor progression, were observed. Discussion: The results of our study suggest that measurements of serum cfDNA and DII using LINE-1 might be valuable new biomarkers for monitoring OMM progression in dogs. This preliminary study demonstrated the potential clinical utility of monitoring plasma cfDNA in canine patients with OMM.